Popular but precarious: low helmet use among shared micromobility program riders in San Francisco - Frye, Willow; Chehab, Lara; Feler, Joshua; Wong, Laura; Tan, Amy; Alpers, Benjamin; Patel, Devika; von Hippel, Christiana; Sammann, Amanda (Frontiers in Public Health, 2024)
Background: Shared micromobility programs (SMPs) are integral to urban transport in US cities, providing sustainable transit options. Increased use has raised safety concerns, notably about helmet usage among e-scooter and e-bicycle riders. Prior studies have shown that head and upper extremity injuries have risen with SMP adoption, yet data on helmet use remains sparse. Methods: This cross-sectional observational study evaluated helmet use among 5,365 riders (ebicycles, conventional bicycles, and e-scooters) in San Francisco during February and March 2019.Observations were made at seven key intersections during peak commute hours on clear days.The majority rode conventional bicycles (77.1%), followed by e-bicycles (19.0%) and escooters (3.9%). Most vehicles (82.2%) were personally owned, with the remainder shared via SMPs. Helmet usage was substantially lower among SMP riders, with shared e-scooter users showing the lowest compliance. Specifically, shared e-scooter riders wore helmets 70% less frequently than personal e-scooter riders and 59% less than shared e-bike riders. Dockless e-bike riders used helmets 42% less than those on docked e-bikes.This study exposes significant gaps in helmet usage among SMP riders, highlighting a pressing need for public health interventions and policy adjustments to improve safety and reduce head injury risks. The findings suggest that helmet use is notably deficient among e-scooter and dockless e-bicycle riders, underscoring the urgent need for targeted safety regulations as cities continue to integrate SMPs into their transportation frameworks.